Meninjau Ulang Wacana Spiritualitas dan Perempuan - Rohmaniyah, Inayah (Sunan Kalijaga State Islamic University & The Asia Foundation, 2008)
This paper explores the concept of spirituality and its relation to feminism, and investigates feminist critics upon religion and women's spirituality in the history of institutionalized religion. It eventually examines the important role of Muslim women's reading on the authenticity of women's spirituality in Islam. Spirituality has to do with an age,old human quest to seek fulfillment in the process of being human, liberation and pointers towards transcendence. Feminism emerged as a new awareness in understanding reality and questioned the existing of androcentric, sexist and patriarchal construction of religion and spirituality. Women's involvement in the process of reading religious texts is imperative in attempt to produce more egalitarian and just reading. Muslim Women's readings arrive at conclusion that the authenticity of one's spirituality, female and male, is determined by one's piety (taqwa) which is identified by one's ability to recognize constraints and preserve equilibrium within her/his life. Piety is the ability to balance individual autonomous reasoning with social hegemony and the natural divine laws, to balance the moral-religious exhortation with reason, knowledge and experience, to balance the heart and mind. It has no relation with gender or sex.